Religious Character as a Control for Moral Degradation of Learners in the Globalization Era - Zakiah Permatasari Rambe (Program Pascasarjana UMSB, 2022)
Globalization on the one hand has a good impact on human life, but on the other hand, globalization often has a bad impact on generations, namely behaviors that tend to adopt outside cultures that enter without caring about regional cultures and national cultures. In line with this statement, this study aims to reveal how religious character can be a bulwark or control over the moral degradation of learners. The research was conducted with a qualitative approach of ethnographic type. The results of the study are, first, the religious character in Islamic boarding schools is developed in various forms, both intracurricular and extracurricular. Second, students in Islamic boarding schools have a strong religious character, so they are not easily influenced by cultures that are contrary to religious teachings. Third, the aspects that support the realization of a strong religious character in Islamic boarding schools are the discipline applied, the geography that is not easily accessible by the contamination of outside cultures, strong cooperation between all resources. The recommendation of this study is that educational institutions must strengthen the religious character of students, because with a strong religious character, it has been proven to be a bulwark of moral degradation of students in the era of globalization.